British Students' Academic Writing: Can Academia Help Improve the Writing Skills of Tomorrow's Professionals?. (April 2013) - Sultan, Nabil
The problem of poor academic writing among British university students is a major cause of concern for universities and their tutors; and it is also of concern to employers struggling to recruit individuals able to communicate clearly and accurately. This article reports on a study designed to highlight some of the reasons for the lack of writing skills, with a view to identifying remedial measures that could be taken to address the problem. The object of the study is an Academy (secondary school) in the North of England, referred to as Northland Academy (NA), one of the new Academies first introduced by the Labour Government in 2000 and now enthusiastically endorsed and promoted in England by the current UK Coalition Government. A first group of students at NA was given relatively simple tests of punctuation and word selection and essay writing; and, separately, a second group was presented with a research proposal and given the task of writing an essay on it. It is suggested that a change in Government policy is needed in order to emphasize and include the importance of academic writing for secondary and FE students intending to progress into HE.